Production performance of indonesian eel Anguilla bicolor bicolor with the addition of calcium carbonate (CaCO3) in to the culture media - Andre Rachmat Scabra; Tatag Budiardi; Daniel Djokosetiyanto (Jurnal Akuakultur Indonesia)
ABSTRACT